If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-13x + -37) = -9(-46 + 4x) Reorder the terms: -3(-37 + -13x) = -9(-46 + 4x) (-37 * -3 + -13x * -3) = -9(-46 + 4x) (111 + 39x) = -9(-46 + 4x) 111 + 39x = (-46 * -9 + 4x * -9) 111 + 39x = (414 + -36x) Solving 111 + 39x = 414 + -36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36x' to each side of the equation. 111 + 39x + 36x = 414 + -36x + 36x Combine like terms: 39x + 36x = 75x 111 + 75x = 414 + -36x + 36x Combine like terms: -36x + 36x = 0 111 + 75x = 414 + 0 111 + 75x = 414 Add '-111' to each side of the equation. 111 + -111 + 75x = 414 + -111 Combine like terms: 111 + -111 = 0 0 + 75x = 414 + -111 75x = 414 + -111 Combine like terms: 414 + -111 = 303 75x = 303 Divide each side by '75'. x = 4.04 Simplifying x = 4.04
| 3x+x+16=50 | | 4y=-5x+-20 | | (7t+5)-(3t-5)= | | 3x+3y+4=x+2y+1 | | 4x-8=-2x-5 | | (x-6)(x+6)=(x-6)(x-6) | | (x-6)(x+6)=(x-6)x(x-6) | | y-5.9=7.22 | | 8x+18=30 | | 2x^4y^2z^2= | | 0=9x+0.25y | | 3Xsquare-13X-10=0 | | 3y^2-11y-30=0 | | 4+25=100 | | 2(3z+3)=(2+1)(3-5) | | 5f+20-6f-30= | | X-3y=36 | | 20=12((5-x)+x+(4-x))+10-((5-x)+x+(6-x))+11-((4-x)+x+(6-x)) | | 20=(12((5-x)+x+(4-x)))+(10-((5-x)+x+(6-x)))+(11-((4-x)+x+(6-x))) | | 9x-5x-8=360 | | 7x-13-x=5 | | x=5x-25 | | 9x-5x-8= | | 5x+25=7x+50 | | -20z+28=25-16z-12+2z-6z | | y=x^2+m-4x | | 3*2+2=7*2-6 | | 2p+3-3p+8= | | a^2-6a+6=0 | | a^2-8a+b^2-2b+17=0 | | 9a^2-6a+b^2-2b+2=0 | | 35=-10+2x |